Mini Cutting Force Sensor: A Novel Approach for Predicting Cutting Forces of Agricultural Products - Putri, Irriwad; Putri, Renny Eka; Makky, Muhammad; Santosa, Santosa (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2025)
Innovation in agricultural mechanization is crucial for the sustainable development of agricultural machinery in Indonesia. This study aims to design and develop a cutting force measurement device for agricultural products. The device consists of a mechanical system utilizing a linear actuator (5.88 mm/s) as a blade pusher and a control system employing a load cell as a force sensor. Testing was conducted using three blade types with cutting angles of 10°, 15°, and 20° on taro, chayote, and papaya. Measurement data were displayed as graphs on an LCD and stored as XLS files on an SD card. The tested materials had moisture content ranging from 85% to 95%. Results showed that taro required the highest cutting force (74.3 N), followed by chayote (39.77 N) and papaya (31.1 N), corresponding to their hardness and moisture content. In contrast, the highest cutting speed was observed in chayote (6.1 mm/s), followed by papaya (5.8 mm/s) and taro (3.5 mm/s) using a 20° blade. These findings confirm that harder materials with lower moisture content require greater cutting force than softer materials with higher moisture content. Keywords: Controller, Cutting force, Load cell, Mechanization, Small-scale.